Some Modified Versions of Durbins H-Statistic - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1985)
This paper proposes a modified version of Durbin's h-statistic for testing residual correlation in a dynamic regression model. Finite sample properties of the new statistic, Durbin's h-statistic and Sargan's modified version of h are investigated by simulation.